Oncologic outcomes of laparoscopic gastrectomy: a single-center safety and feasibility study - Matsuhashi, Nobuhisa (Springer-Verlag, 2013)
BACKGROUND: Indications for laparoscopic gastrectomy (LG) for early stomach cancer have spread worldwide and evaluation of short-term outcomes has been favorable. The present study aimed to evaluate both technical feasibility and safety of LG and short-and long-term outcomes after LG. METHODS: The study group comprised 231 patients who underwent LG during the period from August 2001 through December 2011 at Gifu University School of Medicine. RESULTS: Concomitant resection of other organs was performed in 16 (6.9 %) of the 231 patients, and conversion to open surgery was performed in 5 (2.2 %) patients. The final clinical stage of the patients, according to the Union for International Cancer Control classification, was stage IA in 183 (79.0 %), stage IB in 26 (11.3 %), stage IIA in 9 (2.6 %), stage IIB in 6 (2.6 %), stage IIIA in 5 (2.2 %), and stage IIIB in 2 (0.9 %) patients. Average values of total blood loss and operation time were 133.7 ± 129.0 ml and 328.1 ± 70.1 min, respectively. Postoperative complications were detected in 29 patients (12.6 %), and one patient died. According to the Clavien–Dindo classification of surgical complications, the rate of severe complications of grade ≥3a was 6.1 % and that of grade ≥3b was 1.3 %. There were no significant differences in complications in relation to clinicopathological or operative procedures. Cancer recurrence was detected in 2 (0.9 %) patients. In the patient with peritoneal dissemination, tumor size and macroscopic type were critical. Five-year overall survival rates were 99.3 % for stage IA, 95.2 % for stage IB, and 50.0 % for stage IIB patients. One recurrence each was detected for stages IA and IIB cancers. CONCLUSION: The present study showed LG to have a safe postoperative course and to benefit oncologic outcomes.